Effectiveness of Toulmin’s Argumentation Pattern (TAP) with Snowball Media on Student Learning Outcomes in Acid-Base - Husna, Ariza Rafidah; Watulingas, Maasje Chaterine; Rahmadani, Agung (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The enhancement of classroom learning achievements can be attained through the implementation of instructional approaches that are both efficient and aligned with students specific requirements. This study focuses to evaluate how effectively the integration of the Toulmin’s Argumentation Pattern (TAP) framework with snowball-based media on students achievement in acid-base material. The novelty of this study lies in the direct integration of snowball media within the TAP argumentative framework. Previous research has applied TAP or snowball separately, but no studies have combined both approaches into a single structured model, particularly for acid-base material. This integration introduces a new instructional innovation that merges systematic reasoning with interactive peer engagement. The TAP learning model will encourage students to develop structured reasoning and critical thinking, while snowball media is used to increase interaction between students through fun and collaborative question and answer activities. Pre-experimental research used a one group pretest-posttest design involving 36 students of class XI-D SMAN 7 Samarinda selected through purposive sampling based on class activity and schedule suitability. Data analysis included normality test, N-Gain, and effect size calculation. The average learning outcomes increased from 7.22 in the pretest to 69.16 in the posttest. The average N-Gain value is 0.67 indicate moderate improvement, while the Effect Size value is 4.91 showed a very high impact. These results confirm that TAP learning design combined with snowball media is highly effective in improving student learning outcomes on acid-base materials.